Family Medicine as a Model of Primary Health Services Delivery: A Pilot Study in Almaty, Kazakhstan - Dilara Orynbassarova (University Library System, University of Pittsburgh, 2015)
Introduction. Advanced models of delivering primary health care are being implemented in various countries of the world. This is especially true for countries undergoing a healthcare transition in Central Asia, such as Kazakhstan, which obtained independence from Soviet Union in 1991. The Kazakhstan National Program of Health Reform, implemented between 2005-2010, aimed to create an effective system of primary care. One of the key directions of healthcare reform implemented in Kazakhstan included the development of family medicine, which has become cutting-edge agenda for Kazakhstan Health Ministry over the past 10 years. While many papers have been published about the importance of family medicine and primary healthcare models, few have focused on analyzing family medicine effectiveness in Kazakhstan and its impact on access to family doctor services and patient satisfaction. The key aims of this pilot investigation were 1) to assess the model's impact on access to primary care and patients' satisfaction, and 2) to explore the model's effectiveness in some Central Asian and transitional countries in the literature.  Methods. This pilot study was based on semi-structured interviews and questionnaires about the perception and impact of the primary care model to 86 respondents aged 19-51 (54% females, 46% males). The majority of respondents were Almaty city residents (71%), while the rest were Almaty Province rural residents (22%) and residents of other Kazakhstan regions (7%). Results. Respondents from rural areas associated general practitioners, or family doctors, with community clinics (also referred to as feldsher posts). Even though urban area respondents use family doctor services, they were more likely to get those services in private rather than public clinics. Rural residents appear to have better access to primary care providers than urban residents participating in our study. Also, respondents from rural areas were more satisfied with services provided by family doctors than respondents from urban areas. Conclusions. This pilot study helped to improve our understanding of primary health care reforms implemented in Kazakhstan, a topic that is not traditionally covered in international literature. This pilot study suggests that primary care is more effectively implemented in rural areas of Kazakhstan (Almaty Province); however, future full-scale research in this area is needed to fully understand the complexity of primary healthcare access in Kazakhstan.